The Effect of Profit Sharing Fund, Export Value, Capital Expenditure Investment in Economic Growth and Unemployment in East Kalimantan - Anwar Arifin Pinem; Muhammad Saleh; Aji Sofyan Effendy (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This study discusses 1 To determine the effect of Profit Sharing Funds, Export Value on Economic Growth, Capital Expenditure on Economic Growth investment on unemployment through Economic Growth in East Kalimantan Design/methodology/approach: This research is a quantitative research and data analysis using path analysis regression Findings: Profit Sharing Funds, Export Value, Capital expenditure has no effect on economic growth and investment has a significant effect on economic growth in East Kalimantan Province. : Profit Sharing Funds, Export Value, Capital expenditure and investment has no significant effect on unemployment in East Kalimantan Province. profit sharing funds, export value, capital expenditure and investment have an indirect effect on unemployment through economic growth in East Kalimantan Province. Research limitations/implications: There are six variables considered in this paper: Profit Sharing Funds, Export, Capital Expenditure, investment, Economic Growth unemployment Practical implications: partially corporate governance has no effect and macroeconomics has a negative effect. Originality/value: This study calculates and finds out the truth of Profit Sharing Funds, Export, Capital Expenditure, investment, Economic Growth unemployment